Structural Model of Teacher Work Productivity Based on Discipline and Compensation - Khoirul Anwar; Abd Syakur; Istiyati Mahmudah; Achmad Agus Priyono (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
Persistent challenges in improving teachers' work productivity motivate this study. This study aims to examine how work discipline and compensation both partially and simultaneously affect teachers' work productivity. A quantitative approach was used in the study, using a survey method. Data was gathered using a structured questionnaire that was tested for validity and reliability in order to ensure the accuracy and consistency of the measurement instruments. Multiple linear regression techniques were used to analyze the data before they were preceded by classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests, in order to ensure that the regression model met the requirements. The results indicate that work discipline has a positive and significant effect on teachers’ work productivity. Likewise, compensation is proven to have a positive and significant influence on productivity. Simultaneously, work discipline and compensation significantly affect teachers’ work productivity, with a relatively strong explanatory power based on the coefficient of determination, indicating that a substantial proportion of variations in teachers’ productivity can be explained by these two variables. These findings emphasize that improving teachers’ work productivity requires not only consistent enforcement of work discipline but also a fair and adequate compensation system. The originality of this study lies in the integrated analysis of work discipline and compensation within the context of public secondary education, supported by comprehensive empirical evidence. This contribution enriches the literature on educational management and provides practical implications for school leaders and policymakers in formulating strategies to enhance teachers’ productivity in a systematic and sustainable manner